Peran Net Interest Margin dalam Memediasi Pengaruh Efisiensi Operasional dan Likuiditas terhadap Kinerja Keuangan Bank Konvensional di Indonesia 2020-2024 - Putri Lestari; Purnamawati Purnamawati (Jurnal Kajian Ilmu Manajemen (JKIM), 2026)
This study aims to analyze the effect of operational efficiency and liquidity on financial performance with Net Interest Margin as a mediating variable in conventional banks listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using secondary data obtained from the annual financial reports of conventional banks. The population consists of all conventional banks listed on the Indonesia Stock Exchange, while the sample is determined using purposive sampling based on specific criteria. Operational efficiency is measured using the Operating Expenses to Operating Income ratio, liquidity is proxied by the Loan to Deposit Ratio, financial performance is represented by Return on Assets, and Net Interest Margin serves as the mediating variable. Data analysis is conducted using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach version 4.1.1.6. The results indicate that operational efficiency has a significant negative effect on Net Interest Margin but does not significantly affect financial performance. Liquidity has a significant positive effect on Net Interest Margin but does not significantly influence financial performance. Furthermore, Net Interest Margin has a significant positive effect on financial performance and is proven to mediate the effect of operational efficiency and liquidity on financial performance.